Pemetaan Literatur Sistem Digital Pemantauan Anak: Menyusun Kerangka Kebutuhan untuk Platform E-Kesehatan Terintegrasi di Indonesia - Suyoso, Gandu Eko Julianto; Selviyanti, Erna; Pratama, Mudafiq Riyan; Yunus, Muhammad (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2026)
Background: Child growth and development monitoring is a fundamental intervention in preventing stunting and developmental delays. Although various digital systems have been developed, fragmentation between physical growth and child development monitoring remains a major challenge. Objective: This study aims to map the research landscape of digital systems for child growth and development monitoring and identify gaps and the most frequently appearing system requirements in the literature. Method: A systematic mapping study was conducted on six data sources consisting of direct access and Publish or Perish searches, including Scopus, Scopus via PoP, PubMed, PubMed via PoP, IEEE Xplore, and Web of Science via PoP for the 2020-2025 period. A total of 16 research articles were analyzed using VOSviewer for bibliometric mapping and thematic analysis for system requirements identification. Results: The mapping revealed six research clusters with digital health positioned peripherally. Temporal analysis showed a shifting focus toward mental health integration, stunting prevention, and digital tool utilization. Three main gaps were identified: the peripheral position of digital health, separation between growth and development domains, and dominance of observational studies. The most dominant functional requirements were growth monitoring (12 articles) and developmental screening (11 articles), while usability (9 articles) was the main non-functional priority. Conclusion: Integration of growth and development monitoring in a single platform remains understudied. The resulting requirements list can serve as an initial reference for future integrated system development.